Improved Spatial Modulation with Mapping Diversity - Yılmaz, Mümtaz (Fırat Üniversitesi, 2024)
In this work, mapping diversity technique is exploited for generalized spatial modulation. In this context, multiple constellations, obtained as the solution of the optimization problem that maximizes Euclidean distance between the elements of the signal set, are employed in the active transmit antennas of generalized spatial modulation scheme. Supported with analytical analysis and simulation results, the proposed scheme is shown to enhance the error rate performance of conventional generalized spatial modulation.

Bu çalışmada genelleştirilmiş uzaysal modülasyon için eşlemleme çeşitlemesi tekniğinden faydalanılmıştır. Bu kapsamda, genelleştirilmiş uzaysal modülasyon şemasındaki aktif iletim antenlerinde sinyal kümesindeki elemanlar arası Öklit mesafesini maksimize eden optimizasyon probleminin çözümü olarak elde edilen çoklu işaret kümeleri kullanılmıştır. Tasarlanan şemanın geleneksel uzaysal modülasyon tekniğinin hata oranı performansını iyileştirdiği analitik analiz ve benzetim sonuçları ile desteklenerek gösterilmiştir.
Eşlemleme Çeşitlemesi ile İyileştirilmiş Uzaysal Modülasyon
Keywords: Wireless Communication Systems and Technologies (Incl. Microwave and Millimetrewave); Kablosuz Haberleşme Sistemleri ve Teknolojileri (Mikro Dalga ve Milimetrik Dalga dahil)